The impact of cuts to social care spending on the use of accident and emergency departments in England - Rowena Crawford; George Stoye; Ben Zaranko (Institute for Fiscal Studies (IFS), 2018)
Recent years have seen substantial reductions in public spending on social care for older people in England. This has not only led to large falls in the number of people over the age of 65 receiving publicly funded social care, but also to growing concern about the potential knock-on effects on other public services, and in particular the National Health Service (NHS). In this paper, we exploit regional variation in the reductions in public funding for social care to examine the impact on Accident and Emergency (A&E) departments in NHS hospitals. We find that reductions in social care spending on people aged 65 and above have led to increased use of A&E services, both in terms of the average number of visits per resident and the number of unique patients visiting A&E each year. We estimate that the average cut to social care spending for the older population over the period (375) led to an increase of 0.09 visits per resident, compared to a mean of 0.37 visits in 2009. The effects are most pronounced among people aged 85 and above. This has also led to a modest increase in the cost of providing A&E care, increasing A&E costs by an additional 3 per resident for each 100 cut in social care funding.
Keywords: 330